Pd‐Catalyzed Surface Reactions of Importance in Radiation Induced Dissolution of Spent Nuclear Fuel Involving H2. Issue 20 (25th September 2019) - Maier, Annika Carolin; Jonsson, Mats
Abstract: To assess the influence of metallic inclusions (ϵ‐particles) on the dissolution of spent nuclear fuel under deep repository conditions, Pd‐catalyzed reactions of H2 O2, O2 and UO2 2+ with H2 were studied using Pd‐powder suspensions. U(VI) can efficiently be reduced to less soluble U(IV) on Pd‐particles in the presence of H2 . The kinetics of the reaction was found to depend on the H2 partial pressure at pH2 ≤5.1×10 −2  bar. In comparison, the H2 pressure dependence for the reduction of H2 O2 on Pd also becomes evident below 5.1×10 −2  bar. Surface bound hydroxyl radicals are formed as intermediate species produced during the catalytic decomposition of H2 O2 on oxide surfaces. While a significant amount of surface bound hydroxyl radicals were scavenged during the catalytic decomposition of H2 O2 on ZrO2, no scavenging was observed in the same reaction on Pd. This indicates a different reaction mechanism for H2 O2 decomposition on Pd compared to metal oxides and is in contrast to current literature. While Pd is an excellent catalyst for the synthesis of H2 O2 from H2 and O2, a similar catalytic activity that was previously proposed for ZrO2 could not be confirmed. Abstract : Understanding nuclear fuels : Pd catalyzes UO2 2+ and H2 O2 reduction even at low H2 partial pressures. Catalytic decomposition of H2 O2 on Pd has a different mechanism than on metal oxides. While Pd catalyzes H2 O2 formation from its elements, the same catalytic activity that was proposed for ZrO2 could not be confirmed.